Does suicidal ideation increase during the second COVID-19 lockdown?. (July 2021) - Efstathiou, Vasiliki; Michopoulos, Ioannis; Yotsidi, Vasiliki; Smyrnis, Nikolaos; Zompola, Christina; Papadopoulou, Athanasia; Pomini, Valeria; Papadopoulou, Marianna; Tsigkaropoulou, Evdoxia; Tsivgoulis, Georgios; Douzenis, Athanasios; Gournellis, Rossetos
Abstract: This longitudinal study aimed to investigate the predictive factors of suicidal ideation during the second lockdown in Greece. The respondents presented a 4.32% suicidal ideation in the second lockdown, which did not differ significantly to the initial 4.81%. Anxiety, depression, suicidal ideation during the first lockdown and living with a person with frail health and vulnerable for COVID-19 severe infection emerged as significant risk factors for suicidal ideation during the second lockdown, after controlling for gender, age, and mental health history. Depression was found as the only significant prognostic factor for suicidal ideation incidence of the second lockdown.